تقسيم الألفاظ باعتبار دلالتها على المعنى المستعمل فيه في ضوء القرائن المقاصدية _دراسة تحليلية تطبيقية_ - الدّين, أ.م. د. بختيار نجم الدّين شمس; غفار, جلال جمال (Sulaimani Journal for Humanities, 2023)
This study addresses a significant subject: connecting texts' purposes and foresight. This is a delicate topic because there are some texts for which one interpretation is drawn from their surface meaning while another interpretation is drawn from their deeper meaning and purpose. There is no denying that when there are no previous assumptions, it is easier to remember the essential meaning of any paragraph. However, this superficial interpretation is often not the discourse's original intent and does not serve the context. What truly assists us is a clear, purposeful presupposition from this seeming basic meaning, transforming it into a profound goal that the context intended. The Islamic Ummah (Nation) may experience difficulty due to failing to comprehend these deep goals and may commit many errors and deviations and differ on various topics.